Ugotavljanje antropogenega stresa pri bukvi (Fagus sylvatica l.) v Zasavju - Bienelli-Kalpič, Andreja (Zbornik gozdarstva in lesarstva, 2006)
Common Beech (Fagus sylvatica L.) is the prevailing tree species in Slovenia and central Europe and thus highly appropriate as air pollution bioindicator. With its structure and function it reflects the environmental conditions and represents the supplemental measurements of physical-chemical measurements of air pollutants in the environment. Zasavje area is one of the more polluted areas in Slovenia due to industry (mining, thermal power plant, glass factory,chemical industry). The sampling sites were chosen in the vicinity of ecological information system of Trbovlje Thermal Power Plant, were air pollutants and meteorological parameters are continuously measured. Preža at Kočevska Reka was chosen as reference sampling site. The condition of samplingtrees was determined by biochemical parameters of anthropogenic stress(photosynthetic pigments, antioxidants) and macronutrients supply. The result showed stress of trees due to anthropogenic pollution by statistical higher content of total sulphur, watersoluble thiols in beech leaves and lowercontent of photosynthetic pigments. The trees were well or optimally supplied by macronutrients at all sampling plots.
Keywords: biondikacija; bukev; Fagus sylvatica L.; kemijska analiza; onesnaževanje; Zasavje